Long-term Effects of Perinatal Androgenization on Reproductive Parameters of Male Rat Offspring Androgenization and Male Rat Reproduction - Guerra, M. T.; Perobelli, J. E.; Sanabria, M.; Anselmo-Franci, J. A.; De Grava Kempinas, W. (Hormone and Metabolic Research, 2013)
It is known that during sex differentiation, fetal androgens are critical determinants of the male phenotype. Although testosterone is necessary for normal development of male sexual behavior, perinatal androgen treatment can result in disruption of normal male sexual reproduction. Pregnant Wistar rats were administered either corn oil (vehicle) or testosterone propionate at 0.2 mg/kg from gestational day 12 until the end of lactation and the reproductive function of male offspring was evaluated at 90 (adulthood) and 270 (middle age) days of age. Perinatal androgenization in the rat provoked a reduction in sperm production and reserves in adulthood that did not affect fertility and did not persist at more advanced ages, as shown by the results at post-natal day 270. If perinatal androgenization promotes similar effects in humans of reproductive age, the results of the present work can impact male reproduction health, given the less efficient spermatogenesis and lower sperm reserves in the human epididymis, compared to rodents.
Keywords: rat male offspring; perinatal androgenization; sperm counts; sexual behavior; fertility